(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The COVID-19 pandemic caused an unprecedented disruption in global education systems and accelerated the transformation of teaching methodologies worldwide. According to UNESCO, more than 1.6 billion learners in over 190 countries were affected by school and university closures during the peak of the pandemic. This article provides a comparative methodological analysis of remote and traditional classroom learning in the post-pandemic educational environment. The study examines key factors such as teaching effectiveness, student engagement, academic achievement, digital competence, communication quality, and socio-psychological development. Research findings demonstrate that remote learning significantly improved technological literacy, independent learning skills, and flexibility in educational access. However, several international studies revealed that prolonged online education negatively affected students’ motivation, concentration, interpersonal communication, and mental well-being. In contrast, traditional classroom learning remained more effective in maintaining collaborative interaction, active participation, and emotional support within the educational process. The article also highlights that educational inequalities became more visible during the pandemic due to differences in internet access and digital infrastructure. Based on comparative analysis, the study concludes that hybrid education, which combines digital technologies with face-to-face pedagogical interaction, represents the most sustainable and effective model for future education systems. The research findings may contribute to the development of innovative pedagogical strategies and the improvement of educational quality in the post-pandemic era.